Response of corn to different levels of nitrogen and sowing methods - Abdul Hadi Omran; Anchal Dass (Annals of Agricultural Research, 2025)
A field experiment was conducted at the Agronomy Research Farm of the Agricultural Faculty of Albieroni University in Kapisa Province, Afghanistan, to study the response of maize to sowing methods and nitrogen fertilizer levels during the spring season of 2022and 2023. Three sowing methods (broadcast sowing, ridge sowing, and line sowing) and four levels of nitrogen (0, 120, 160, and 200 kg N ha-¹) were applied. The experiment was laid out in a well-prepared field using a Randomized Complete Block Design with a split arrangement, having three replications. Sowing methods were assigned to the main plots, while nitrogen levels were assigned to the split plots. Maximum plant height, leaf area index, number of green leaves, 1000- seed weight, grain yield, Stover yield, and biological yield were recorded in the ridge sowing method along with the application of 200 kg N ha-¹ when compared with other treatments. It can be concluded from these results that the ridge sowing method and nitrogen fertilizer at the rate of 200 kg ha-¹ produced an economical crop of maize under the climatic conditions of Kapisa Province, Afghanistan